Enantioselective Total Synthesis of the Morphogen (−)-Thallusin and Mediated Uptake of Fe(Iii) into the Green Seaweed Ulva - Morales-Reyes, C (John Wiley and Sons Inc, 2024)
A fully enantioselective, catalytic synthesis of the algal morphogen (−)-thallusin using polyene cyclization chemistry is reported. The synthesis features dedicated precursor design, introduction of a TMS-substituted arene as a regioselective terminator, very high enantiomer excess (ee) on gram scale, and productive scaffold functionalization. Furthermore, an ee determination methodology of thallusin samples was developed, and the ee of biosynthesized thallusin was determined. Fe(III)-uptake studies demonstrated that the cellular uptake of iron facilitated by thallusin derivatives was independent of their morphogenic activity, suggesting their active import via siderophore transporters as a shuttle system. © 2024 The Authors. Chemistry - A European Journal published by Wiley-VCH GmbH.